Estudo de caso sobre a educação de surdos na cidade de Estreito - MA. - Serra, Rafaela de Lima da Silva (Universidade Federal do Tocantins, 2022)
In recent years, much has been said about bilingualism aimed at the educational process of deaf people, that is, a teaching and learning process in which the deaf student has access to school contents through sign language, as a language of instruction, and Portuguese, as the written support language. In view of this, knowing that there are legal documents that support the right of deaf people to include their official language in the educational scope, and that this makes students have access to quality education, we determined the need to study the inclusion process of deaf students in the teaching network of Estreito/MA, after 20 years of the Law that recognized the Brazilian Sign Language as an official language. To accomplish this, our work sought to understand how the educational process for the deaf community in the city of Estreito/MA is, to identify the number of deaf students enrolled in the education teaching network of Estreito/MA, to know the training of teachers who teach classes for deaf students of schools in the municipal network and verify the existence of any project related to bilingual education for the deaf in schools that serve deaf students. To measure this, we gather data from the Secretary of Education and Culture of the city, as well as from the bilingual schools of São Luís and Imperatriz/MA, where we were able to learn about the progress of language education in the municipality, and the challenges that still must be met in order to offer high quality education to deaf people.